(untitled) (Applied Biological Research, 2023)
Soybean has ten maturity loci governing its flowering time, maturity and photoperiodism. The E1 and E3 maturity loci delay maturity and induce photoperiod sensitivity, while their mutants are vice versa. In a field trial of 17 genotypes during kharif 2016, two early (JS 95-60 and JS 20-34) and two late maturing genotypes (MAUS 61 and MACS 1188) were identified for further molecular analysis. Full-length 525 bp E1 gene and partial 1688 bp E3 gene coding sequence were amplified, and sequence analysed along with reference sequence of early maturing Harosoy. In the partial E3 gene coding sequence studied, 26 substitution SNPs were observed, none of which was maturity specific. In E1 coding sequences, 87 substitution SNPs were observed, of which 17 SNPs were earliness specific conserved among JS 20-34, JS 95-60 and early Harosoy. Similarly, six amino acid frame polymorphisms were found to be earliness specific shared amongst them. Typical B3-like conserved domains with 11 trimeric DNA binding sites were found in the E1 gene within 172-504 and 178-504 bases interval intervals in early and late varieties, respectively. Thus, the molecular characterization of E1 maturity locus in local genotypes of soybean can contribute for more efficient plant breeding.